In factorization, we write the middle term of the quadratic equation either as a sum of two numbers or difference of two numbers such that the equation can be factorized.
⇒ (√3x)2 – 2√6x + (√2)2 = 0
⇒ (√3x - √2)2 = 0
⇒ x =
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Introduction to Linear Equations in Two Variables62 mins
Pair of Linear Equations-Yahaan se laye marks57 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation